The relationship between the functional status of regulatory mechanisms and the effectiveness of technical and tactical operations in boxers - Shchedrina, Y. A.; Melnikov, D. S.; Seliverstova, V. V.; Aimbetova, N. V. (Theory and Practice of Physical Culture, 2025)
Objective of the study - is to analyze the interrelationships between psychophysiological parameters and characteristics of heart rate variability, which affect the effectiveness of technical and tactical actions of boxers during competitions.